Archetypal Roles of an Abscisic Acid Receptor in Drought and Sugar Responses in Liverworts. Issue 1 (15th November 2018) - Jahan, Akida; Komatsu, Kenji; Wakida-Sekiya, Mai; Hiraide, Mayuka; Tanaka, Keisuke; Ohtake, Rumi; Umezawa, Taishi; Toriyama, Tsukasa; Shinozawa, Akihisa; Yotsui, Izumi; Sakata, Yoichi; Takezawa, Daisuke
Abstract : The receptor for abscisic acid, which regulates seed dormancy and stomatal closure, mediates desiccation tolerance and sugar responses in liverworts that represent early diverging lineages of embryophytes. Abstract: Abscisic acid (ABA) controls seed dormancy and stomatal closure through binding to the intracellular receptor Pyrabactin resistance1 (Pyr1)/Pyr1-like/regulatory components of ABA receptors (PYR/PYL/RCAR) in angiosperms. Genes encoding PYR/PYL/RCAR are thought to have arisen in the ancestor of embryophytes, but the roles of the genes in nonvascular plants have not been determined. In the liverwort Marchantia polymorpha, ABA reduces growth and enhances desiccation tolerance through increasing accumulation of intracellular sugars and various transcripts such as those of Late Embryogenesis Abundant ( LEA )-like genes. In this study, we analyzed a gene designated Mp PYL1, which is closely related to PYR / PYL / RCAR of angiosperms, in transgenic liverworts. Transgenic lines overexpressing Mp PYL1 - GFP showed ABA-hypersensitive growth with enhanced desiccation tolerance, whereas Mp pyl1 generated by CRISPR-Cas9-mediated genome editing showed ABA-insensitive growth with reduced desiccation tolerance. Transcriptome analysis indicated that Mp PYL1 is a major regulator of abiotic stress-associated genes, including all 35 ABA-induced LEA -like genes. Furthermore, these transgenic plants showed altered responses to extracellular Suc, suggesting that ABA and PYR/PYL/RCAR function in sugar responses. The results presented here reveal an important role of PYR/PYL/RCAR in the ABA response, which was likely acquired in the common ancestor of land plants. The results also indicate the archetypal role of ABA and its receptor in sugar response and accumulation processes for vegetative desiccation tolerance in bryophytes.